Peranan Humas Pemerintahan (Government Public Relations) dalam Menciptakan Reputasi Pemerintahan yang Baik - Oktri Permata Lani; Benni Handayani (Universitas Serang Raya, 2021)
The role of government public relations in the era of technological and information advancement is now no longer as a transmitter of information, but as a strategic element in supporting the successful implementation of government programs. Especially creating a reputation for good governance in the community. Therefore, the role of Public Relations Public Relations needs to be developed to be more proactive so that it is able to package information, oblique news that develops in the community and straighten it according to true, balanced and proportional facts so that people do not have bad perceptions about the government. The focus of the problem is the role of government public relations (Government Public Relations) in creating a good government reputation in the eyes of the community, as well as the objectives and functions of Government Public Relations (Government Public Relations) in creating a good government reputation in the eyes of the public. The research method uses literature study. Public Relations is designed based on serious research, planning and evaluation. The work process of Public Relations is a continuous circular process, and is a continuous process in the form of a spiral. In the implementation of the function of public relations or Public Relations requires, a variety of reliable expertise, people who can be trusted, supervision, coordination, attention to every detail and carried out in a professional manner. Public Relations must be able to master technical skills in disseminating information to achieve the goals that have been determined by the Public Relations. In this approach, Public Relations can use various communication channels, including interpersonal, public, group communication, mass media, both print and audio-visual and New Media.